100 citation classics in Energy and Fuels - Konur, Özcan (SILA SCIENCE, 2012)
The present study explores the characteristics of 100 citation classics in Energy and Fuels published between 1945 and 2011 based on the Arts & Humanities Citation Index (A&HCI), Science Citation Index Expanded (SCIE), and Social Sciences Citation Index (SSCI) and its implications using the scientometric techniques, complementing a scientometric study of the global Energy and Fuels research. The results of this study reveal that a paper by Miller & Bowman (1989) on the nitrogen chemistry in combustion published in Progress in Energy and Combustion Science (journal ranking no: 1) had 1,565 citations with 65.2 citations per year. 56 of these classics were published after 2000 and 44 of them were published between 1972 and 1999. The number of publications made a peak between 2000 and 2004 with 37 papers. 44 and 56 of the citation classics were reviews and articles, respectively. The US and Europe were the major players with 45 and 31 citation classics, respectively, together having 76 classic papers. The US was over-represented and Europe, China, and Japan were underrepresented in citation classics. There were 75 institutions worldwide producing citation classics in Energy and Fuels and 13 of them produced 38 citation classics. University of California was the most prolific institution with 8 classics. 5 journals published 65% of the citation classics and Journal of Power Sources (journal ranking no: 10) was the most prolific journal publishing 17 citation classics mostly in the area of energy storage and fuel cells. These five most prolific journals were overrepresented in citation classics where 18 journals produced 100 citation classics. "Krebs FC" and "Westbrook CK" had 4 classics each. 69 of the classics had 2 or more authors. Engineering, Electrochemistry, and Thermodynamics were other prolific subject areas. Citation classics had more applied sciences and interdisciplinary focus. There were 25 papers on the energy storage and fuel cells, closely followed by 24 papers on the biofuels and 19 papers on the combustion, 14 papers each on petroleum and solar cells, and 5 papers on waste treatment. The scientometric analysis has a great potential to gain valuable insights into the evolution of the citation classics in Energy and Fuels, complementing the scientometric studies in the fields of the renewable energies as well as other dynamic research fields providing a unique insight on the incentive structures for all the key stakeholders in the field.
Keywords: Energy; Fuels; Research evaluation; Web of Knowledge; Research productivity; Scientometrics